Adverse effects of a 10‐day course of ibuprofen in Holstein calves. Issue 5 (14th February 2016) - Walsh, P.; Carvallo Chaigneau, F. R.; Anderson, M.; Behrens, N.; McEligot, H.; Gunnarson, B.; Gershwin, L. J.
Abstract : Nonsteroidal anti‐inflammatory drugs (NSAIDs) are recommended for various conditions in cattle. Ibuprofen is an inexpensive short‐acting NSAID and is readily available in liquid formulation for administration to bottle‐fed calves. We compared the adverse effects of a 10‐day course of ibuprofen and placebo in 16 five‐ to six‐week‐old Holstein bull calves that were being treated for experimentally induced bovine respiratory syncytial virus infection. Ibuprofen was administered as a liquid in milk replacer at 30 mg/kg divided three times daily. We found an increased prevalence of abomasal ulceration 5 of 8 in the ibuprofen compared to placebo group 2 of 6 ( P  = NS). There was one (1 of 8) case of mild interstitial nephritis in the ibuprofen and none (0 of 8) in the placebo group ( P  = NS). Renal function as measured by serum BUN and creatinine levels was not different between groups; no animal demonstrated an increase in creatinine.